Virtual tour based in augmented reality as a biology learning media - Aishiyah Saputri Laswi; B. Bungawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
This study aims to see the validity and practicality of augmented reality-based virtual tour biology learning media. Media was developed specifically for the introduction of cell organelles. This research applies Research and Development research and uses the Interactive Multimedia System Design and Development method as the system development method. The steps for developing IMSDD are system requirements, design considerations, implementation and evaluation. The research was conducted at MAN Palopo with research subjects of eleventh class of math and science with 24 students in total. Data collection techniques include observation, interviews and questionnaires using interview guide instruments, observation sheets and questionnaire sheets. Data analysis techniques are carried out qualitatively and quantitatively. The research results (1) The validity of media after going through the validation test stage by the two experts, namely 96.16% is in the valid category, (2) The results of the practicality test by students obtained results of 87.83% in the very practical category, while the results of the practicality test by the teacher obtained a result of 96% in the very practical category. The presence of augmented reality-based virtual tour media in the introduction of cell organelle material is able to facilitate students in recognizing each microscopic cell organelle so that it appears real. The use of Augmented Reality based virtual tours in learning allows students to learn independently outside the classroom and can increase the learning experience to be more interactive and interesting for students.